PENGARUH CO-PRECIPITATION BESI KLORIDA TERHADAP KINERJA LUMPUR AKTIF PADA PROSES PENGOLAHAN AIR LIMBAH DOMESTIK SINTETIK - Dian Fatikha Aristiami; I Nyoman Widiasa (Dept. of Chemical Engineering, Diponegoro University, 2015)
The increase of population leads to an increase of the quantity of domestic wastewater. Activated sludge system is the most cost-efective to treat the domestic wastewater treatment. This study is aimed to evaluate the co-precipitation coagulant effect of FeCl3 on the growth of activated sludge, settling characteristics of the activated sludge, and effluent quality. sludge sedimentation characteristics (settling) as well as on the effluent quality. The activated sludge systems were operated in batch mode and synthetic domestic wastewaters with C:N:P ratio of 100:5:1 were used as feed wastewater. The growth of activated sludge was based on concentration of Mixed Liquor Suspended Solid (MLSS), settling characteristics of activated sludge was based on value of Sludge Volume Index (SVI), and effluent quality was based on turbidity, colour, N-ammonia concentration, and Chemical Oxygen Demand content. Results indicate that inhibition effect of FeCl3 to activated sludge activity was not significant at dosage ≤ 30 mg/L. Good settling characterisic (SVI 70-150 mg/L) was achieved at dosage of 20-30 mg/L. Finally, the best effluent quality, i.e. turbidity (9.4), colour (96), amonia removal (83.6%), and COD removal (72.97%), at dosage of 30 mg/L. Keywords: activated sludge; co-precipitation; domestic wastewater; wastewater treatment Abstrak Peningkatan jumlah penduduk mengakibatkan kenaikan jumlah air limbah domestik. Sistem lumpur aktif merupakan proses yang paling efektif untuk mengolah air limbah domestik. Penelitian ini bertujuan untuk mengevaluasi pengaruh co-precipitation koagulan FeCl3 terhadap pertumbuhan lumpur aktif, karakteristik pengendapan lumpur aktif, dan kualitas efluen. Sistem lumpur aktif dioperasikan secara curah dan umpan air limbah yang digunakan adalah air limbah domestik sintesis dengan rasio C:N:P = 100:5:1. Pertumbuhan lumpur aktif berdasarkan konsentrasi Mixed Liquor Suspended Solid (MLSS), karakteristik pengendapan lumpur berdasarkan nilai Sludge Volume Index (SVI), dan kualitas efluen berdasarkan tingkat kekeruhan, warna, kadar N-amonia dan kadar Chemical Oxygen Demand (COD). Hasil penelitian menunjukkan bahwa inhibisi FeCl3 terhadap aktivitas lumpur aktif tidak signifikan pada dosis ≤ 30 mg/L. Karakteristik pengendapan yang baik (SVI 70-150 mg/L) tercapai pada dosis 20-30 mg/L. Kualitas efluen terbaik, yaitu kekeruhan (9,4), warna (96), penyisihan amonia (83,6%) dan penyisihan COD (72,97%), pada dosis 30 mg/L. Kata kunci: lumpur aktif; co-precipitation; air limbah domestik; pengolahan air limbah